PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Lilis Suryani; Emy Yunita Rahma Pratiwi (Kampus Akademik Publiser, 2024)
The development of this learning media is a type of research and development that creates products to provide guidance to support an interactive learning process using the encouragement of a future product. is a strategic effort in the field of education to increase the effectiveness and efficiency of the teaching and learning process. Learning media can be in the form of books, videos, audio or other visual aids which function as mediators that connect teachers with students, facilitating increases in students' knowledge, skills and competencies. The use of appropriate and innovative learning media can stimulate students' thoughts, feelings and attention, making the learning process more interesting and interactive, this can ultimately increase student learning outcomes. This development uses the example of the Borg and Gall development where data and issue collection is carried out by means of interviews, observations, questionnaires, documentation and other additions such as test results. As for carrying out data analysis, previously a prerequisite test was carried out to determine the use of the formula, namely by carrying out a t test.